2007
DOI: 10.1007/s10549-007-9764-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in manganese superoxide dismutase, myeloperoxidase and glutathione-S-transferase and survival after treatment for metastatic breast cancer

Abstract: Treatments for metastatic breast cancer (MBC) are primarily palliative with variable efficacy and outcomes may be influenced by individual differences in drug metabolism. In this study, we examined the association of single nucleotide polymorphisms (SNPs) in genes involved in drug metabolism with progression free survival (PFS) and breast cancer specific survival (BCSS) in 95 patients with MBC that received high dose chemotherapy (HDC) with autologous stem cell transplantation (ASCT). SNPs in the SOD2 (SOD2-01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Comparison between studies is complicated by the inclusion of different SNPs in different genes. Prior studies have shown that some variants in CYPs and GSTs can alter the pharmacokinetics of CTX metabolism [27, 29, 30] and influence clinical response and toxicity of CTX-based chemotherapies [31–38]. Other studies have found no association between genetic variants in these genes and CTX pharmacokinetics [39] or outcome [40].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between studies is complicated by the inclusion of different SNPs in different genes. Prior studies have shown that some variants in CYPs and GSTs can alter the pharmacokinetics of CTX metabolism [27, 29, 30] and influence clinical response and toxicity of CTX-based chemotherapies [31–38]. Other studies have found no association between genetic variants in these genes and CTX pharmacokinetics [39] or outcome [40].…”
Section: Discussionmentioning
confidence: 99%
“…These are listed in Table 1 and have been previously described (Bewick et al 2006(Bewick et al , 2008. The clinical trials and study were approved by the Research Ethics Board, Sudbury Regional Hospital, Sudbury, Ontario, and informed signed consent was obtained from all patients.…”
Section: Patient Populationmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in genes in these pathways may significantly affect DNA repair efficiency (Au et al 2004;Abdel-Rahman and El-Zein 2000;Duell et al 2000), drug toxicity and clinical outcomes following treatment with cancer drugs and/or radiation (Booton et al 2006;Ambrosone et al 2006;Gurubhagavatula et al 2004;Kamikozuru et al 2008). The influence of individual gene polymorphisms on treatment outcome may be moderate, but reports from our laboratory (Bewick et al 2006(Bewick et al , 2008 and others Ambrosone et al 2005;Nagle et al 2007;Nowell et al 2005) suggest that combinations of polymorphisms in several genes may significantly impact clinical responses and survival.…”
Section: Introductionmentioning
confidence: 99%
“…By reading the full texts, 11 studies were out of scope as they did not satisfy the inclusion criteria (one meeting abstract, three animal experiments or cell cultures and seven without available data). Finally, a total of 34 publications were available for the present meta-analysis, 26 for risk analysis and eight for survival analysis (58)(59)(60)(61)(62)(63)(64)(65). The flow chart of study search and inclusion was demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%